Can podocytes be regenerated in adults?. Issue 3 (May 2017) - Shankland, Stuart J.; Freedman, Benjamin S.; Pippin, Jeffrey W.
Abstract : Purpose of review: Podocytes are critical components of the nephron filtration barrier and are depleted in many kidney injuries and disease states. Terminally differentiated adult podocytes are highly specialized, postmitotic cells, raising the question of whether the body has any ability to regenerate lost podocytes. This timely question has recently been illuminated by a series of innovative studies. Here, we review recent progress on this topic of significant interest and debate. Recent findings: The innovation of genetic labeling techniques enables fate tracing of individual podocytes, providing the strongest evidence yet that podocytes can be replaced by nearby progenitor cells. In particular, two progenitor pools have recently been identified in multiple studies: parietal epithelial cells and cells of renin lineage. These studies furthermore suggest that podocyte regeneration can be enhanced using ex-vivo or pharmacological interventions. Summary: Recent studies indicate that the podocyte compartment is more dynamic than previously believed. Bidirectional exchange with neighboring cellular compartments provides a mechanism for podocyte replacement. Based on these findings, we propose a set of criteria for evaluating podocyte regeneration and suggest that restoration of podocyte number to a subsclerotic threshold be targeted as a potentially achievable clinical goal.